A Fish Assemblage from the Middle Eocene from Libya (Dur At-Talah) and the Earliest Record of Modern African Fish Genera. - Olga Otero; Aurélie Pinton; Henri Cappetta; Sylvain Adnet; Xavier Valentin; Mustapha Salem; Jean-Jacques Jaeger (PLoS ONE, 2015)
In the early nineteen sixties, Arambourg and Magnier found some freshwater fish (i.e., Polypterus sp., Siluriformes indet. and Lates sp.) mixed with marine members in an Eocene vertebrate assemblage at Gebel Coquin, in the southern Libyan Desert. This locality, aged ca 37-39Ma and now known under the name of Dur At-Talah, has been recently excavated. A new fish assemblage, mostly composed of teeth, was collected by the Mission Paléontologique Franco-Libyenne. In this paper, we describe freshwater fish members including a dipnoan (Protopterus sp.), and several actinopterygians: bichir (Polypterus sp.), aba fish (Gymnarchus sp.), several catfishes (Chrysichthys sp. and a mochokid indet.), several characiforms (including the tiger fish Hydrocynus sp., and one or two alestin-like fish), and perciforms (including the snake-head fish Parachanna sp. and at least one cichlid). Together with the fossiliferous outcrops at Birket Qarun in Egypt, the Libyan site at Dur At-Talah reduces a 10-Ma chronological gap in the fossil record of African freshwater fish. Their fish assemblages overlap in their composition and thus constitute a rather homogenous, original and significant amount of new elements regarding the Paleogene African ichthyofauna. This supports the establishment of the modern African freshwater fish fauna during this time period because these sites mostly contain the earliest members known in modern genera.